SMALL DENSE LDL AS INDICATORS OF DIABETIC NEPHROPATHY PREVENTION EFFORTS TO PATIENT TYPE 2 DIABETES MELLITUS - Pemula, Giok (Majority, 2014)
Abstract Diabetic nephropathy (ND) is one of the complications of diabetes mellitus (DM) in the kidney which ended in kidney failure. It is the 6th leading cause of death in western countries. In 2005, Ditjen Yanmed Depkes RI showed that DM is ranked top among other metabolic diseases, the number of events around 42,000 cases and caused the death of about 3,316 people. The early stages of the pathogenesis of ND, the formation of advanced glycosylation end products (AGEs) in the kidney causes crosslinks so intertitium and plasma proteins are not glycosylated trapped. Trapping of small dense low-density lipoprotein (sd-LDL), causing this protein cannot be pushed out of the walls of blood vessels and promote the deposition of cholesterol in the intima. AGEs also cause the migration of monocytes, release of cytokines and growth factors from macrophages, increased endothelial permeability, fibroblasts and smooth muscle cells and extracellular matrix synthesis which can affect the structure and function of the glomerular capillaries in the kidney to form glomerulosclerosis. This situation will reduce the blood flow resulting in glomerular basement membrane permeability changes that marked the onset of albuminuria. Sd-LDL levels in patients with type 2 diabetes with the incidence of atherosclerosis is 41,89 mg/dL. This value can be used as an indicator to prevent the formation of glomerulosclerosis in the process of kidney damage. Keywords: atherosclerosis, diabetes mellitus, diabetic nephropathy, small dense LDL Abstrak Nefropati diabetika (ND) adalah salah satu komplikasi dari diabetes mellitus (DM) pada ginjal yang berakhir pada gagal ginjal. Merupakan penyebab kematian ke-6 di negara barat. Pada tahun 2005, Direktorat Jendral Pelayanan Medis Departemen Kesehatan Republik Indonesia menunjukkan bahwa DM berada di peringkat paling atas di antara penyakit metabolik lain, angka kejadiannya sekitar 42.000 kasus dan menyebabkan kematian sekitar 3.316 jiwa. Tahap awal patogenesis ND, pembentukan advanced glicosylation end products (AGEs) di ginjal menyebabkan terjadinya ikatan silang sehingga protein intertitium dan plasma yang tidak terglikoksilasi terperangkap. Terperangkapnya small dense lipoprotein densitas rendah (sd-LDL), menyebabkan protein ini tidak dapat terdorong keluar dari dinding pembuluh darah dan mendorong pengendapan kolesterol di intima.AGEs juga menimbulkan migrasi monosit, pengeluaran sitokin dan faktor pertumbuhan dari makrofag, peningkatan permeabelitas endotel, fibroblas dan sel otot polos serta sintesis matriks ekstrasel dimana dapat mempengaruhi struktur dan fungsi kapiler di glomerulus ginjal sehingga terbentuk glomerulosklerosis. Keadaan ini akan mengurangi aliran darah sehingga terjadi perubahan permeabilitas membran basalis glomerulus yang ditandai timbulnya albuminuria.Kadar sd-LDL pada pasien DM tipe 2 dengan angka kejadian aterosklerosis yaitu 41,89 mg/dL. Nilai ini dapat dijadikan indikator untuk mencegah terbentuknya glomerulosklerosis dalam proses kerusakan ginjal. Kata kunci:aterosklerosis, diabetes mellitus, nefropati diabetika, small dense LDL